2007
DOI: 10.1042/bj20061591
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for a metallohydrolase mechanism in which the nucleophile is not delivered by a metal ion: EPR spectrokinetic and structural studies of aminopeptidase from Vibrio proteolyticus

Abstract: Metallohydrolases catalyse some of the most important reactions in biology and are targets for numerous chemotherapeutic agents designed to combat bacterial infectivity, antibiotic resistance, HIV infectivity, tumour growth, angiogenesis and immune disorders. Rational design of inhibitors of these enzymes with chemotherapeutic potential relies on detailed knowledge of the catalytic mechanism. The roles of the catalytic transition ions in these enzymes have long been assumed to include the activation and delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 53 publications
(71 reference statements)
3
20
0
Order By: Relevance
“…As the electronic environment of Co(II) changes due to coordination geometry and site symmetry, the EPR lineshape is a sensitive reporter of the local environment in Co(II)-substituted metalloenzymes [3336]. Co(II) in biologically relevant, pseudo-octahedral environments typically has a large zero-field splitting ( DS z 2 ≫ gβBS ), such that only the lowest M S = |± 1/2> Kramers doublet is observable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the electronic environment of Co(II) changes due to coordination geometry and site symmetry, the EPR lineshape is a sensitive reporter of the local environment in Co(II)-substituted metalloenzymes [3336]. Co(II) in biologically relevant, pseudo-octahedral environments typically has a large zero-field splitting ( DS z 2 ≫ gβBS ), such that only the lowest M S = |± 1/2> Kramers doublet is observable.…”
Section: Resultsmentioning
confidence: 99%
“…This high pH sample could be simulated using g iso = 2.35, E/D = 0.10† within the standard spin Hamiltonian: H^=βB0gS+D[Sz213S(S+1)+ED(Sx2Sy2)]+SAI, where β is the Bohr magneton, B 0 the applied magnetic field, S the spin operator, D the axial zero-field splitting, E/D the rhombicity of the zero-field splitting, A the hyperfine coupling constant for 59 Co, and I the nuclear spin of 59 Co. These electronic parameters were reasonable for axial Co(II), in which the value for | D | was much larger than the Zeeman splitting [33, 36]. This likely arose from the 6C center which contained one H 2 O ligand.…”
Section: Resultsmentioning
confidence: 99%
“…A recent theoretical study 49 suggested that the nucleophilic water molecule in the B2 MβLs is activated by a metal-liganding oxygen atom of a carboxylate rather than directly by a Zn(II) ion; an analogous mechanism was proposed for the B3 lactamase GOB from E. meningoseptica 26 and for another metallohydrolase, aminopeptidase from Vibrio , on the basis of crystallographic and EPR spectrokinetic studies. 50 The latter study, in particular, highlighted the role of the metal center in activating substrate, proposing that as the primary role for the metal center rather than nucleophile activation and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The most intensively studied and well characterized of these enzymes is the 32kD secreted di-zinc leucine aminopeptidase, VpAP, from Vibrio proteolyticus (formerly Aeromonas proteolytica ) [36-40]. It appears that one of the metal ions in VpAP and related mAPs is involved in nucleophile activation, and is essential for catalysis, whereas the other is involved in substrate activation and stabilization of the transition state [36, 39, 41]; the non-essential metal ion may thus be key to substrate specificity, though conclusive evidence is lacking. Other dinuclear mAPs that have been studied include the angiogenesis target methionyl aminopeptidase, and the secreted aminopeptidases that are virulence factors in the pathogenicity of certain species of Clostridium, Streptomyces, Vibrio and Aeromonas [42-48].…”
Section: Introductory Statementmentioning
confidence: 99%
“…Some potent inhibitors of VpAP and its homologs, including bestatin (ubenimex), ovalicin, and fumagillin, have also been shown to exhibit in vivo activity against tumor growth, angiogenesis, and HIV infectivity [8, 24, 51-59]. Wild-type VpAP is readily available in large quantities from V. proteolyticus , and it is an excellent model protein with which to explore the structure-function relationships of mAPs: studies on VpAP have provided information that may lead to the design of more effective and specific chemotherapeutic agents [35, 39-41, 60]. However, recent work on VpAP and VpAP homologs has shown that site-directed recombinant variants can provide important mechanistic information that is unavailable with the native proteins [61-64].…”
Section: Introductory Statementmentioning
confidence: 99%